Altered functional differentiation of mesoangioblasts in a genetic myopathy. Issue 3 (7th February 2013) - Altomare, Claudia; Barile, Lucio; Rocchetti, Marcella; Sala, Luca; Crippa, Stefania; Sampaolesi, Maurilio; Zaza, Antonio
Abstract Mutations underlying genetic cardiomyopathies might affect differentiation commitment of resident progenitor cells. Cardiac mesoangioblasts (cMabs) are multipotent progenitor cells resident in the myocardium. A switch from cardiac to skeletal muscle differentiation has been recently described in cMabs from β‐sarcoglycan‐null mice (βSG−/−), a murine model of genetic myopathy with early myocardial involvement. Although complementation with βSG gene was inconsequential, knock‐in of miRNA669a (missing in βSG−/− cMabs) partially rescued the mutation‐induced molecular phenotype. Here, we undertook a detailed evaluation of functional differentiation of βSG−/− cMabs and tested the effects of miRNA669a‐induced rescue in vitro. To this end, cMabs were compared with neonatal cardiomyocytes (CMs) and skeletal muscle C2C12 cells, representative of cardiac and skeletal muscle respectively. Consistent with previous data on molecular patterns, electrophysiological and Ca2+‐handling properties of βSG−/− cMabs were closer to C2C12 cells than to CM ones. Nevertheless, subtler aspects, including action potential contour, Ca2+‐spark properties and RyR isoform expression, distinguished βSG−/− cMabs from C2C12 cells. Contrary to previous reports, wild‐type cMabs failed to show functional differentiation towards either cell type. Knock‐in of miRNA669a in βSG−/− cMabs rescued the wild‐type functional phenotype, i.e. it completely prevented development of skeletal muscle functional responses. We conclude that miRNA669a expression, ablated by βSG deletion, may prevent functional differentiation of cMabs towards the skeletal muscle phenotype.